Les évolutions de l’américanisme toulousain depuis les années 1980 - Soizic Croguennec (Caravelle)
Americanism appears to be a strong scholarly tradition at Toulouse 2 University. Indeed, both the different formations offered through the IPEALT recently transformed into IPEAT, and the dynamic investigations represented by the PhD thesis defended in the domain of Humanities for the last decades are the unmistakable signs of such a tradition. However, one must admit that Americanism in Toulouse 2 is anything but a monolithic interest. As a consequence, one has to study the evolution of the researchers’ interrogations both from a chronological point of view and from a disciplinary one.